Doses subletais de metomil sobre Spodoptera frugiperda (Lepidoptera: Noctuidae) e Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) - Rodrigues, Raimundo Henrique Ferreira (2023)
Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) is a key pest in crops such as soybeans and corn. Damage includes reduction in stand, leaf area and production. The main control tool consists of the use of insecticides, of which Methomyl is commonly used. However, application failures such as droplet drift or degradation can expose insects to sublethal concentrations. These two aspects can favor the selection of resistant populations. The use of natural enemies is a tool that can be used for pest control, in which the parasitoid Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae), is used to control lepidopteran pests in crops such as soybeans and corn. In the present study, it was identified that the exposure of S. frugiperda to sublethal concentrations (LC5, LC15 and LC30) of Methomyl negatively affects the percentage of larval survival and the adult reproduction rate. A population of S. frugiperda collected in the field, in the city of Guaraciaba do Norte (CE), was exposed to the sublethal LC50 concentration of the active ingredient Methomil for 11 generations and, in the seventh generation, the biological parameters were determined. A reduction of 50.0 and 45.0% in the fecundity and fertility of females was detected in relation to the control, respectively. No negative effect of sublethal concentrations of Methomyl was observed on the parasitoid T. pretiosum. Exposure of S. frugiperda to sublethal concentrations of Methomyl resulted in low resistance, according to the Resistance Ratio. However, even though resistance was classified as low, the existence of an adaptive cost was verified, and it was observed that the development and reproduction of the resistant S. frugiperda population were negatively affected in relation to the susceptible population. The population exposed to sublethal concentrations of Methomyl did not show multiple resistance to the active ingredients Chlorfenapyr, Metaflumizone and Teflubenzuron. Eggs of S. frugiperda from the resistant population were offered for parasitism by T. pretiosum, and compared to the susceptible population. In this study, it was determined that S. frugiperda eggs from the Methomyl-Resistant population did not affect parasitism, emergence and sex ratio. The functional response of T. pretiosum in S. frugiperda eggs from the Methomyl-resistant and susceptible populations were Type II, and the handling time was the same, only the attack rate was lower in the Methomyl-Resistant population. Therefore, sublethal doses of Methomyl affect the biology of S. frugiperda, but did not affect the behavior of the parasitoid T. pretiosum. Exposure of S. frugiperda to the sublethal concentration of Methomyl after 11 generations did not result in resistance, but the insects belonging to this population showed changes in biological parameters, and there was no multiple resistance to the active ingredients. The supply of eggs from the Methomyl-resistant S. frugiperda population did not alter the parasitism, emergence and functional response of T. pretiosum.